Boron oxide coated quaternary positive electrode material, its manufacturing method and use
A boron oxide coating on quaternary cathode materials addresses the issue of poor cycle stability by ensuring uniform coating and minimizing electrolyte contact, improving battery performance and reducing costs through a low-temperature sintering process.
Patent Information
- Application Number
- JP2022556524
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-12
- Filing Date
- 2022-01-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-01-20
AI Technical Summary
High-nickel quaternary cathode materials in lithium-ion batteries suffer from poor cycle stability due to lithium precipitation, uneven coating, and increased surface area leading to intense side reactions with the electrolyte, which degrade battery performance.
A boron oxide coating is applied to the surface of quaternary cathode materials through a two-stage low-temperature oxidation sintering process using metaboric or pyroboric acid, ensuring uniform coating and reducing the contact area with the electrolyte, thereby minimizing side reactions and improving cycle stability.
The boron oxide coating effectively reduces side reactions during charging and discharging, enhances cycle stability, and maintains the electrical properties of the cathode material while reducing energy consumption and manufacturing costs.
Smart Images

Figure 0007603705000002 
Figure 0007603705000003 
Figure 0007603705000004
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of lithium ion batteries, and in particular to boron oxide coated quaternary positive electrode materials, their preparation and use. [Background technology]
[0002] Lithium-ion batteries are currently the most widely applied electrochemical power source, and the most representative of these batteries are lithium secondary batteries (LIBs), which generate electrical energy by changing the chemical potential caused by the absorption and release of lithium ions into and from the positive and negative electrodes. Meanwhile, since the positive electrode material plays a direct leading role in the performance of LIBs, many researchers are working to realize positive electrode materials capable of reversible absorption and release of lithium ions with large capacity, fast charge and discharge rate, and long cycle life. Currently, high-nickel materials are considered the most promising candidate materials because the specific capacity of lithium-ion batteries can be improved by increasing the nickel content. However, the deterioration of the cycle stability of lithium-ion batteries due to the increase in nickel content may hinder the success of this method.
[0003] In addition, among high-nickel materials, quaternary polycrystalline materials have more advantages in terms of safety and cycle stability compared to ternary positive electrode materials, and are currently one of the most promising materials. However, at present, the method of reducing the residual alkalinity of high-nickel quaternary positive electrode materials is mainly by water washing process. After water washing, lithium residue is removed, and there is a large concentration difference between the lithium ions in the lattice and the lithium ions outside the lattice, so the material is prone to delithiation reaction without electron transfer, and therefore Ni 3+ / Ni 2+The conversion of nickel is easy to occur, and after washing, the surface of the material is rough, the specific surface area is large, the contact area with the electrolyte is large, and the side reaction is more intense. To solve this problem, a commonly used modification method is to coat the surface of the material. However, for high-nickel quaternary positive electrode materials, lithium is precipitated on the surface of the material when coated at high temperatures, and the pH increases, so low-temperature coating is required. The common low-temperature coating agent is mainly boric acid, but during the high-speed mixing process of boric acid and positive electrode material, dehydration occurs due to the temperature rise, and the coating on the material surface becomes uneven. Therefore, some high-nickel quaternary positive electrode materials are not coated, and contact with the electrolyte causes side reactions, resulting in deterioration of the cycle stability of the battery. Summary of the Invention [Problem to be solved by the invention]
[0004] The main objective of the present invention is to provide a boron oxide coated quaternary positive electrode material, its preparation method and use, so as to solve the problem of poor cycle stability of the quaternary positive electrode material in the prior art. [Means for solving the problem]
[0005] In order to achieve the above object, according to one aspect of the present invention, a quaternary positive electrode material substrate and a boron oxide coating layer are provided on a surface of the quaternary positive electrode material substrate, and the quaternary positive electrode material substrate is Li a Ni x Co y Mn z Al (1-x-y-z) O2 (wherein a=1 to 1.06, x=0.8 to 0.9, y=0.01 to 0.1, z=0.01 to 0.1).
[0006] Furthermore, the particle size of the quaternary positive electrode material is 8 to 12 μm.
[0007] Furthermore, the boron oxide coating layer has a thickness of 5 to 10 nm.
[0008] According to another aspect of the present invention, a mixture including a quaternary positive electrode material substrate and a boron source is subjected to a first oxidation sintering to obtain a boron oxide-coated quaternary positive electrode material, wherein the quaternary positive electrode material substrate is Li a Ni x Co y Mn z Al (1-x-y-z) O2 (wherein a = 1 to 1.06, x = 0.8 to 0.9, y = 0.01 to 0.1, z = 0.01 to 0.1), and the boron source is one or two selected from metaboric acid and pyroboric acid.
[0009] Furthermore, the sintering temperature of the first oxidation sintering is 150 to 350° C., and the sintering time is 4 to 12 hours.
[0010] Furthermore, the first oxidation sintering is divided into a first stage and a second stage which are performed in sequence, and the sintering temperature of the first stage is lower than that of the second stage.
[0011] Furthermore, the sintering temperature in the first stage is 150 to 200° C., and the sintering time is 1 to 5 hours.
[0012] Furthermore, the sintering temperature in the second stage is 200 to 350° C., and the sintering time is 3 to 7 hours.
[0013] Furthermore, the mass ratio of the boron source to the quaternary positive electrode material substrate is 0.001 to 0.003:1.
[0014] Furthermore, the first oxidative sintering is carried out in a first oxygen-containing gas.
[0015] Furthermore, the volume concentration of oxygen in the first oxygen-containing gas is 20 to 100%, and the flow rate of the first oxygen-containing gas is 10 to 20 L / min.
[0016] Furthermore, the above manufacturing method further includes a mixing step of mixing the quaternary positive electrode material substrate with a boron source to obtain a mixture.
[0017] The mixing step further includes mixing the quaternary positive electrode material substrate and a boron source and performing a first stirring to obtain a mixture of the quaternary positive electrode material substrate and the boron source.
[0018] Furthermore, the speed of the first stirring is 2000 to 3000 rpm, and the duration is 10 to 20 minutes.
[0019] Furthermore, the above manufacturing method further includes a step of manufacturing a quaternary positive electrode material substrate, the manufacturing step comprising: x Co y Mn z Al (1-x-y-z) The mixture of OH and LiOH is subjected to a second oxidation sintering to obtain a quaternary cathode material substrate.
[0020] Furthermore, the above LiOH and Ni x Co y Mn z Al (1-x-y-z) The molar ratio to OH is 1 to 1.5:1.
[0021] Furthermore, the sintering temperature of the second oxidation sintering is 650 to 800° C., and the sintering time is 4 to 12 hours.
[0022] Furthermore, the second oxidative sintering is carried out in a second oxygen-containing gas.
[0023] Furthermore, the volume concentration of oxygen in the second oxygen-containing gas is 20 to 100%, and the flow rate of the second oxygen-containing gas is 5 to 10 L / min.
[0024] Furthermore, the above manufacturing method further includes a step of washing the quaternary positive electrode material substrate, and the washing step includes performing a second stirring on the dispersion liquid containing the washing liquid and the quaternary positive electrode material substrate, and then drying.
[0025] Furthermore, the second stirring is performed at a speed of 200 to 400 rpm for a duration of 5 to 15 minutes.
[0026] Furthermore, the drying temperature is 100 to 200° C., and the drying time is 5 to 15 hours.
[0027] Furthermore, the cleaning liquid contains water.
[0028] According to a further aspect of the present invention, there is provided a lithium ion battery comprising a positive electrode material, a negative electrode material, and an electrolyte, the positive electrode material comprising a quaternary positive electrode material, the quaternary positive electrode material being any of the boron oxide coated quaternary positive electrode materials described above or a boron oxide coated quaternary positive electrode material produced by any of the production methods described above. Effect of the Invention
[0029] The technical solution of the present invention is to oxidize and sinter a boron source containing metaboric acid and / or pyroboric acid together with a quaternary positive electrode material substrate, so that metaboric acid and pyroboric acid release less water at high temperatures than boric acid, and thus, when forming a boron oxide coating layer by oxidizing and sintering, there is no problem that the viscosity of the system increases due to the release of water by boric acid, making it difficult to uniformly mix the boron source and the quaternary positive electrode material substrate, and thus, it is possible to uniformly coat the quaternary positive electrode material substrate, effectively reducing the contact area between the quaternary positive electrode material substrate of the boron oxide-coated quaternary positive electrode material after oxidizing and sintering and the electrolyte, thereby reducing side reactions on the surface of the quaternary positive electrode material during charging and discharging, and improving the cycle stability of the positive electrode material. In addition, metaboric acid and pyroboric acid require less water to be removed than boric acid, and thus the reaction efficiency of the oxidizing and sintering is improved. [Brief description of the drawings]
[0030] The drawings in the specification which form a part of this application are provided for a further understanding of the present invention, and the illustrative embodiments of the present invention and the description thereof are intended to interpret the present invention and are not intended to unduly limit the present invention. [Figure 1] 1 shows a scanning electron microscope image of the quaternary positive electrode material produced in Example 1 of the present invention. [Diagram 2] 1 shows the initial charge and discharge curves of the quaternary positive electrode material prepared in Example 1 of the present invention. [Diagram 3] 1 shows the initial charge and discharge curves of the quaternary positive electrode material prepared in Comparative Example 1 of the present invention. [Figure 4] FIG. 2 is a temperature rise curve diagram of the one-stage oxidation sintering of the boron oxide-coated quaternary positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] In addition, the embodiments and features of the embodiments of the present application may be combined with each other unless there is a contradiction. MODE FOR CARRYING OUT THE PRESENT DISCLOSURE The present invention will now be described in detail with reference to the accompanying drawings.
[0032] As described in the background art of this application, in the prior art, in the coated quaternary positive electrode material produced using boric acid as a raw material, a part of the quaternary positive electrode material is exposed due to uneven coating, and during use, this exposed part of the quaternary positive electrode material undergoes a violent side reaction with the electrolyte, resulting in a decrease in the cycle performance of the lithium-ion battery. In order to solve the above problems, this application provides a boron oxide coated quaternary positive electrode material, its manufacturing method and use.
[0033] According to a representative embodiment of the present application, a quaternary positive electrode material substrate and a boron oxide coating layer are provided on the surface of the quaternary positive electrode material substrate, and the quaternary positive electrode material substrate is Li a Ni x Co y Mn z Al (1-x-y-z) O2 (wherein a=1 to 1.06, x=0.8 to 0.9, y=0.01 to 0.1, and z=0.01 to 0.1).
[0034] There is a uniform and complete boron oxide coating layer on the surface of the quaternary positive electrode material substrate, and the coating layer is a B2O3 coating layer, which effectively reduces the contact area between the quaternary positive electrode material substrate of the boron oxide-coated quaternary positive electrode material and the electrolyte, reduces side reactions on the surface of the quaternary positive electrode material during charging and discharging, and improves the cycle stability of the positive electrode material.
[0035] Since the boron oxide coating layer of the present application is almost free of active material, the proportion of the boron oxide coating layer in the boron oxide-coated quaternary positive electrode material affects its electrical properties. More preferably, the particle size of the quaternary positive electrode material is 8 to 12 μm, and the thickness of the boron oxide coating layer is preferably 5 to 10 nm. The boron oxide-coated quaternary positive electrode material that satisfies the above conditions fully achieves the effect of reducing side reactions caused by boron oxide, while containing a large amount of active material in the material, which gives the material good electrical properties.
[0036] In order to allow those skilled in the art to easily obtain the above-mentioned boron oxide-coated quaternary positive electrode material of the present application, according to another exemplary embodiment of the present application, a mixture including a quaternary positive electrode material substrate and a boron source is subjected to a first oxidation sintering to obtain a boron oxide-coated quaternary positive electrode material, wherein the quaternary positive electrode material substrate is Li a Ni x Co y Mn z Al (1-x-y-z) O2 (wherein a = 1 to 1.06, x = 0.8 to 0.9, y = 0.01 to 0.1, z = 0.01 to 0.1), and the boron source is one or two selected from metaboric acid and pyroboric acid.
[0037] By oxidizing and sintering a boron source containing metaboric acid and / or pyroboric acid together with a quaternary positive electrode material substrate, metaboric acid and pyroboric acid release less water at high temperatures than boric acid, so that when a boron oxide coating layer is formed by oxidizing and sintering, there is no problem that the viscosity of the system increases due to boric acid releasing water, making it difficult to uniformly mix the boron source and the quaternary positive electrode material substrate, and thus a uniform coating can be achieved on the quaternary positive electrode material substrate, effectively reducing the contact area between the quaternary positive electrode material substrate of the boron oxide-coated quaternary positive electrode material after oxidizing and sintering and the electrolyte, reducing side reactions on the surface of the quaternary positive electrode material during charging and discharging, and improving the cycle stability of the positive electrode material. In addition, metaboric acid and pyroboric acid require less water to be removed than boric acid, so that the reaction efficiency of the oxidation sintering is improved.
[0038] In some embodiments, the sintering temperature of the first oxidation sintering is 150-350°C, and the time is 4-12h. By carrying out the oxidation sintering at a low temperature, the problem of lithium precipitation caused by the quaternary positive electrode material being sintered at a high temperature can be avoided, and the loss of lithium in the quaternary positive electrode material substrate can be minimized. Meanwhile, the energy consumption and cost of the entire manufacturing method can be effectively reduced, the process cost can be reduced, and a positive electrode material with better performance can be obtained.
[0039] Considering that metaboric acid and pyroboric acid lose water at high temperatures, in order to ensure the mixing uniformity of boron element and quaternary positive electrode material substrate during water removal while sufficiently removing water, in some embodiments, the first oxidation sintering is divided into a first stage and a second stage which are performed sequentially, and the sintering temperature of the first stage is lower than that of the second stage. The moisture in metaboric acid and pyroboric acid is removed by the low-temperature sintering of the first stage, and then the oxidation sintering reaction is performed at a high temperature. Preferably, the temperature of the first stage sintering is 150-200°C and the time is 1-5h, and preferably, the temperature of the second stage sintering is 200-350°C and the time is 3-7h. In the first stage, oxidation sintering is carried out at the above low temperature to form a uniform melt, which is then coated on the surface of the quaternary positive electrode material substrate, and then the melt is heated to above 200°C to cause an oxidation sintering reaction to form a strongly coated boron oxide coating layer, improving the stability of the bond between the oxide coating layer and the quaternary positive electrode material substrate and increasing the uniformity of the coating layer itself. The above two-stage low-temperature oxidation sintering effectively reduces the contact area between the quaternary positive electrode material substrate and the electrolyte during use, further reducing side reactions, and further improving the capacity and cycle retention rate of the positive electrode material. In addition, the low calcination temperature provides beneficial effects such as energy saving, efficiency, and cost reduction.
[0040] As described above, the ratio of the boron oxide coating layer to the substrate affects the electrical properties of the cathode material, so in order to more accurately control the ratio of both, the mass ratio of the boron source to the quaternary cathode material substrate is preferably 0.001-0.003:1. Since the flow rate and oxygen content of the oxygen-containing gas affect the reaction rate, in order to improve the formation rate and denseness of the coating layer as much as possible and to avoid gas waste, the first oxidation sintering is preferably performed in a first oxygen-containing gas, preferably the volume concentration of oxygen in the first oxygen-containing gas is 20-100%, and the flow rate of the first oxygen-containing gas is 10-20 L / min. By controlling the formation rate of the boron oxide coating layer to an appropriate range within the above numerical range, the uniformity of the coating layer and the bond strength with the substrate are further ensured.
[0041] Prior to sintering the mixture of the quaternary positive electrode material substrate and the boron source, the two may be premixed by mechanical means to improve the uniformity of the mixture. For example, in some embodiments, the above-mentioned manufacturing method further includes a mixing step of mixing the quaternary positive electrode material substrate and the boron source to obtain a mixture. Preferably, the above-mentioned mixing step includes mixing the quaternary positive electrode material substrate and the boron source and performing a first stirring to obtain a mixture of the quaternary positive electrode material substrate and the boron source, and preferably, the speed of the first stirring is 2000 to 3000 rpm and the time is 10 to 20 min. As described above, in the case of coating using boric acid in the prior art, if the stirring speed is high, the boric acid is dehydrated and becomes a high-viscosity molten material, and the coating on the quaternary positive electrode material substrate becomes non-uniform, while even if the stirring speed is reduced, the boric acid is not adequately dispersed. The metaboric acid and pyroboric acid used in the present invention have low hydrogen and oxygen contents, so there is no dehydration due to temperature rise during high speed mixing, and the materials are uniformly mixed.
[0042] LiNi as used herein x Co y Mn z Al (1-x-y-z) O2 may be an existing material in the prior art or may be manufactured by an existing method in the prior art, and in some embodiments, the manufacturing method further includes a step of manufacturing a quaternary positive electrode material substrate, the manufacturing step being carried out by adding Nix Co y Mn z Al (1-x-y-z) The method includes subjecting the mixture of LiOH and NiOH to a second oxidation sintering to obtain a quaternary positive electrode material substrate. x Co y Mn z Al (1-x-y-z) The molar ratio of OH is 1 to 1.5:1, preferably the sintering temperature of the second oxidation sintering is 650 to 800°C, the time is 4 to 12 hours, preferably the second oxidation sintering is performed in a second oxygen-containing gas, preferably the volume concentration of oxygen in the second oxygen-containing gas is 20 to 100%, and the flow rate of the second oxygen-containing gas is 5 to 10 L / min. By producing a quaternary positive electrode material substrate, the form of the substrate material and the ratio of elements can be designed and controlled to produce a substrate material more suitable for the boron oxide coating of the present application, and the electrical properties of the positive electrode material can be further improved.
[0043] In the present application, in order to remove unreacted materials after sintering, the quaternary positive electrode material substrate may be washed by a method commonly used in the prior art, and therefore, in some embodiments, the above manufacturing method preferably further includes a step of washing the quaternary positive electrode material substrate, and the washing step further includes performing a second stirring on the dispersion liquid containing the washing liquid and the quaternary positive electrode material substrate, followed by drying, preferably, the speed of the second stirring is 200-400 rpm and the time is 5-15 min, preferably, the drying temperature is 100-200° C. and the time is 5-15 h, and preferably, the washing liquid contains water. According to the above washing method, the residual alkali can be removed as much as possible.
[0044] According to a further exemplary embodiment of the present application, there is provided a lithium ion battery including a positive electrode material, a negative electrode material, and an electrolyte, wherein the positive electrode material includes a quaternary positive electrode material, which is any of the boron oxide coated quaternary positive electrode materials described above or any of the boron oxide coated quaternary positive electrode materials produced by any of the production methods described above.
[0045] Since the boron oxide-coated quaternary positive electrode material of the present application is uniformly coated with boron oxide, the contact area between the quaternary positive electrode material substrate of the boron oxide-coated quaternary positive electrode material and the electrolyte can be effectively reduced, side reactions on the surface of the quaternary positive electrode material during charging and discharging can be reduced, and the cycle stability of the positive electrode material can be improved.
[0046] The beneficial effects of the present invention will be further described below with reference to examples and comparative examples.
[0047] Example 1 (1) Nickel-cobalt-manganese-aluminum hydroxide (molar ratio: Ni:Co:Mn:Al = 90:7:2:1) and LiOH were dry-mixed in a mixer at a molar ratio of 1:1.025. The dry-mixed material was calcined in a conventional box furnace at 700°C under an oxygen atmosphere (flow rate 20 L / min) for 8 h, then cooled, crushed, and sieved to obtain a quaternary positive electrode material substrate.
[0048] (2) The obtained quaternary positive electrode material substrate and distilled water were mixed in a 1:1 ratio, stirred at 300 rpm for 10 minutes, and then left in a vacuum drying oven at 150°C for 10 hours, dried, and then taken out.
[0049] (3) The dried quaternary positive electrode material substrate and HBO2 were dry mixed in a mass ratio of 1:0.001. In the dry mixing step, the quaternary positive electrode material substrate and HBO2 were first stirred at high speed for 10 min (speed 2500 rpm) to uniformly attach metaboric acid powder to the surface of the nickel-cobalt-manganese-aluminum hydroxide particles. The material after dry mixing was calcined at 180°C in an oxygen atmosphere (flow rate 10 L / min) for 3 h (first stage oxidation calcination), heated to 300°C and kept at that temperature for 5 h (second stage oxidation calcination, see Figure 4 for the specific heating method), cooled, and sieved to obtain boron oxide-coated positive electrode material.
[0050] Example 2 Step (3) was the same as in Example 1, except that the stirring speed of the dry mix was 2000 rpm.
[0051] Example 3 Step (3) was the same as in Example 1, except that the stirring speed of the dry mix was 3000 rpm.
[0052] Example 4 Step (3) was the same as in Example 1, except that the stirring speed of the dry mix was 1000 rpm.
[0053] Example 5 Step (3) was the same as in Example 1, except that the stirring speed of the dry mix was 4000 rpm.
[0054] Example 6 Step (3) was the same as in Example 1, except that the temperature of the first-stage oxidation-calcination was 150°C.
[0055] Example 7 Step (3) was the same as in Example 1, except that the temperature of the first-stage oxidation-calcination was 200°C.
[0056] Example 8 Step (3) was the same as in Example 1, except that the temperature of the first-stage oxidation-calcination was 120°C.
[0057] Example 9 Step (3) was the same as in Example 1, except that the temperature of the first-stage oxidation-calcination was 230°C.
[0058] Example 10 Step (3) was the same as in Example 1, except that the temperature of the second-stage oxidation-calcination was 200°C.
[0059] Example 11 Step (3) was the same as in Example 1, except that the temperature of the second-stage oxidation-calcination was 350°C.
[0060] Example 12 Step (3) was the same as in Example 1, except that the temperature of the second-stage oxidation-calcination was 190°C.
[0061] Example 13 Step (3) was the same as in Example 1, except that the temperature of the second-stage oxidation-calcination was 380°C.
[0062] Example 14 Step (3) was the same as in Example 1, except that the dry-mixed material was calcined at 300° C. under oxygen atmosphere for 8 h, cooled, and sieved to obtain a boron oxide-coated cathode material.
[0063] Example 15 In step (3), the procedure was the same as in Example 1, except that in the first oxidation and calcination step, nickel-cobalt-manganese-aluminum oxide and HBO2 were mixed in a mass ratio of 1:0.003.
[0064] Example 16 In step (3), the procedure was the same as in Example 1, except that in the first oxidation and calcination step, nickel-cobalt-manganese-aluminum oxide and HBO2 were mixed in a mass ratio of 1:0.005.
[0065] Example 17 Step (3) was the same as in Example 1, except that HBO2 was replaced with H2B4O7.
[0066] Example 18 (1) Nickel-cobalt-manganese-aluminum hydroxide (molar ratio: Ni:Co:Mn:Al=90:7:2:1) and LiOH were dry mixed in a mixer at a molar ratio of 1:1.025. The dry mixed material was calcined in a conventional box furnace at 650°C for 12 hours under the condition of introducing oxygen-containing gas (volume concentration of oxygen: 20%, flow rate: 5 L / min). Then, it was cooled, crushed, and sieved to obtain the quaternary positive electrode material substrate LiNi 0.9 Co 0.07 Mn 0.02 Al 0.01 Got O2.
[0067] (2) The obtained quaternary positive electrode material substrate and distilled water were mixed in a 1:1 ratio, stirred at 200 rpm for 15 minutes, and then left in a vacuum drying oven at 100°C for 15 hours, dried, and then taken out.
[0068] (3) The dried quaternary cathode material substrate and HBO2 were dry mixed in a mass ratio of 1:0.001. In the dry mixing step, the quaternary cathode material substrate and HBO2 were first stirred at high speed for 10 min (speed 2500 rpm) to uniformly attach metaboric acid powder to the surface of the nickel-cobalt-manganese-aluminum hydroxide particles. The material after dry mixing was calcined at 180°C for 5 h under conditions of introducing oxygen-containing gas (volume concentration of oxygen 20%, flow rate 5 L / min) (first stage oxidation calcination), then heated to 300°C and kept at that temperature for 7 h (second stage oxidation calcination), cooled, and sieved to obtain boron oxide-coated cathode material.
[0069] Example 19 (1) Nickel-cobalt-manganese-aluminum hydroxide (molar ratio: Ni:Co:Mn:Al=90:7:2:1) and LiOH are dry mixed in a mixer at a molar ratio of 1:1.5. The dry mixed material is calcined in a conventional box furnace at 800°C for 4 hours under conditions of introducing oxygen-containing gas (volume concentration of oxygen 80%, flow rate 20 L / min), then cooled, crushed and sieved to obtain the quaternary positive electrode material substrate Li 1.06 Ni 0.9 Co 0.07 Mn 0.02 Al 0.01 Got O2.
[0070] (2) The obtained quaternary positive electrode material substrate and distilled water were mixed in a 1:1 ratio, stirred at 400 rpm for 5 minutes, and then left in a vacuum drying oven at 200°C for 5 hours, dried, and then taken out.
[0071] (3) The dried quaternary cathode material substrate and HBO2 were dry mixed in a mass ratio of 1:0.001. In the dry mixing step, the quaternary cathode material substrate and HBO2 were first stirred at high speed for 10 min (speed 2500 rpm) to uniformly attach metaboric acid powder to the surface of the nickel-cobalt-manganese-aluminum hydroxide particles. The material after dry mixing was calcined at 180°C for 1 h under conditions of introducing oxygen-containing gas (volume concentration of oxygen 80%, flow rate 20 L / min) (first stage oxidation calcination), heated to 300°C and kept at that temperature for 3 h (second stage oxidation calcination), cooled, and sieved to obtain boron oxide-coated cathode material.
[0072] Comparative Example 1 (1) Nickel-cobalt-manganese-aluminum hydroxide (molar ratio: Ni:Co:Mn:Al = 90:7:2:1) and LiOH were dry-mixed in a mixer at a molar ratio of 1:1.025. The dry-mixed material was calcined in a conventional box furnace at 700°C under oxygen atmosphere for 8 hours, then cooled, crushed, and sieved to obtain a quaternary positive electrode material substrate.
[0073] (2) The obtained positive electrode material was mixed with distilled water in a 1:1 ratio, stirred at 300 rpm for 10 minutes, and then left in a vacuum drying oven at 150°C for 10 hours, dried, and then taken out.
[0074] (3) Nickel-cobalt-manganese-aluminum oxide with a molar ratio of Ni:Co:Mn:Al=90:7:2:1 was dry mixed with H3BO3 at a mass ratio of 1:0.001. In the dry mixing step, the quaternary positive electrode material substrate and H3BO3 were first stirred at high speed for 10 min (speed 2500 rpm) to deposit boric acid powder on the surface of the nickel-cobalt-manganese-aluminum hydroxide particles. The material after dry mixing was calcined at 300°C in an oxygen atmosphere for 8 h, cooled, and sieved to obtain the coated quaternary positive electrode material.
[0075] Comparative Example 2 (1) Nickel-cobalt-manganese-aluminum hydroxide (molar ratio: Ni:Co:Mn:Al = 90:7:2:1) and LiOH were dry-mixed in a mixer at a molar ratio of 1:1.025. The dry-mixed material was calcined in a conventional box furnace at 700°C under oxygen atmosphere for 8 hours, then cooled, crushed, and sieved to obtain a quaternary positive electrode material substrate.
[0076] (2) The obtained positive electrode material was mixed with distilled water in a 1:1 ratio, stirred at 300 rpm for 10 minutes, and then left in a vacuum drying oven at 150°C for 10 hours, dried, and then taken out.
[0077] (3) Nickel-cobalt-manganese-aluminum oxide with a molar ratio of Ni:Co:Mn:Al = 90:7:2:1 was calcined at 300°C in an oxygen atmosphere for 8 h, cooled, and sieved to obtain a quaternary positive electrode material.
[0078] Button battery manufacturing Using the positive electrode materials produced in the above examples and comparative examples, the positive electrode material, carbon black conductive agent, PVDF as binder and NMP were uniformly mixed in a mass ratio of 95:2.5:2.5:5 to produce a battery positive electrode slurry. This slurry was applied onto an aluminum foil with a thickness of 20 to 40 μm, vacuum dried and roll pressed to form a positive electrode plate, lithium metal pieces were used as the negative electrode, and the electrolyte was mixed in a ratio of 1.15M LiPF6EC:DMC (1:1 vol%) to assemble a button battery.
[0079] The electrical properties of the material were measured at 45°C using a battery measurement system manufactured by LANDEN Technology Innovation Center, with the measurement voltage ranging from 3 V to 4.3 V. The formation capacity, capacity at 1 week, 20 weeks, and 50 weeks, and capacity retention rate were measured. The measurement results are shown in Table 1.
[0080] [Table 1]
[0081] As can be seen from the above description, the above embodiments of the present invention achieve the following technical advantages.
[0082] By oxidizing and sintering a boron source containing metaboric acid and / or pyroboric acid together with a quaternary positive electrode material substrate, metaboric acid and pyroboric acid release less water at high temperatures than boric acid, so that when a boron oxide coating layer is formed by oxidizing and sintering, there is no problem that the viscosity of the system increases due to boric acid releasing water, making it difficult to uniformly mix the boron source and the quaternary positive electrode material substrate, and thus a uniform coating can be achieved on the quaternary positive electrode material substrate, effectively reducing the contact area between the quaternary positive electrode material substrate of the boron oxide-coated quaternary positive electrode material after oxidizing and sintering and the electrolyte, reducing side reactions on the surface of the quaternary positive electrode material during charging and discharging, and improving the cycle stability of the positive electrode material. In addition, metaboric acid and pyroboric acid require less water to be removed than boric acid, so that the reaction efficiency of the oxidation sintering is improved.
[0083] The above is merely a preferred embodiment of the present invention, and is not intended to limit the present invention. Those skilled in the art can make various modifications and changes to the present invention. Any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and principles of the present invention shall be included in the patent scope of the present invention.
Claims
1. A first oxidation sintering is performed on the mixture including the quaternary positive electrode material substrate and the boron source to obtain a boron oxide-coated quaternary positive electrode material, wherein the quaternary positive electrode material substrate is Li a Ni x Co y Mn z A (1-x-y-z) O 2 (wherein a=1 to 1.06, x=0.8 to 0.9, y=0.01 to 0.1, z=0.01 to 0.1), and the boron source is one or two selected from metaboric acid and pyroboric acid; further comprising a mixing step of dry mixing the quaternary positive electrode material substrate and the boron source to obtain the mixture; The mixing step comprises: mixing the quaternary positive electrode material substrate and the boron source to perform a first stirring at a speed of 2000 rpm to 3000 rpm for a time of 10 min to 20 min to obtain a mixture of the quaternary positive electrode material substrate and the boron source; The sintering temperature of the first oxidation sintering is 150°C to 350°C, and the time is 4h to 12h; The first oxidation sintering is divided into a first stage and a second stage which are performed sequentially, and the sintering temperature of the first stage is lower than the sintering temperature of the second stage; The method for preparing the boron oxide-coated quaternary positive electrode material is characterized in that the sintering temperature in the first step is 150°C to 200°C, and the sintering time is 1h to 5h.
2. 2. The method according to claim 1, wherein the sintering temperature in the second step is 200° C. to 350° C., and the sintering time is 3 h to 7 h.
3. 3. The method according to claim 1, wherein the mass ratio of the boron source to the quaternary positive electrode material substrate is 0.001-0.003:
1.
4. Further comprising the step of manufacturing the quaternary positive electrode material substrate, The manufacturing process includes: x Co y Mn z A (1-x-y-z) 2. The method of claim 1, further comprising subjecting a mixture of LiOH and LiOH to a second oxidation sintering to obtain the quaternary cathode material substrate.
5. The LiOH and the Ni x Co y Mn z A (1-x-y-z) The method according to claim 4, characterized in that the molar ratio of OH is 1 to 1.5:
1.
6. The method according to claim 5, wherein the second oxidation sintering is performed at a sintering temperature of 650° C. to 800° C. for a time of 4 h to 12 h.
7. The method further comprises the step of washing the quaternary positive electrode material substrate; 2. The method according to claim 1, wherein the washing step includes performing a second stirring on a dispersion containing a washing solution and the quaternary positive electrode material substrate, and then drying the dispersion.
8. The method according to claim 7, characterized in that the speed of the second stirring is 200 rpm to 400 rpm and the time is 5 min to 15 min, and / or the temperature of the drying is 100 ° C to 200 ° C and the time is 5 h to 15 h.
Citation Information
Patent Citations
Layered positive electrode material for lithium-ion battery and preparation method of layered positive electrode material
CN107994212A
Positive electrode material with low surface residual alkali as well as preparation method and application thereof
CN109817914A
Lithium ion secondary battery
JP2017152262A
